The unique Pt(II)-induced nucleolar stress response and its deviation from DNA damage response pathways - Pigg, Hannah C.; Alley, Katelyn R.; Griffin, Christopher R.; Moon, Caleb H.; Kraske, Sarah J.; DeRose, Victoria J. (The Journal of biological chemistry, 2024)
The mechanisms of action for the platinum compounds cisplatin and oxaliplatin have yet to be fully elucidated, despite the worldwide use of these drugs. Recent studies suggest that the two compounds may be working through different mechanisms, with cisplatin inducing cell death via the DNA damage response (DDR) and oxaliplatin utilizing a nucleolar stress–based cell death pathway. While cisplatin-induced DDR has been subject to much research, the mechanisms for oxaliplatin’s influence on the nucleolus are not well understood. Prior work has outlined structural parameters for Pt(II) derivatives capable of nucleolar stress induction. In this work, we gain insight into the nucleolar stress response induced by these Pt(II) derivatives by investigating potential correlations between this unique pathway and DDR. Key findings from this study indicate that Pt(II)-induced nucleolar stress occurs when DDR is inhibited and works independently of the ATM/ATR-dependent DDR pathway. We also determine that Pt(II)-induced stress may be linked to the G1 cell cycle phase, as cisplatin can induce nucleolar stress when cell cycle inhibition occurs at the G1/S checkpoint. Finally, we compare Pt(II)-induced nucleolar stress with other small-molecule nucleolar stress–inducing compounds Actinomycin D, BMH-21, and CX-5461 and find that Pt(II) compounds cause irreversible nucleolar stress, whereas the reversibility of nucleolar stress induced by small-molecules varies. Taken together, these findings contribute to a better understanding of Pt(II)-induced nucleolar stress, its deviation from ATM/ATR-dependent DDR, and the possible influence of cell cycle on the ability of Pt(II) compounds to cause nucleolar stress.